Perceptions of nurses on occupational health hazards and safety practices in Ditsobotla public hospitals in North West province - Takalani Denge; Mahlasela Rakhudu (AOSIS, 2022)
Background: Nurses are the backbone of the healthcare system. During the fulfilment of their duties and responsibilities, they experience various types of work-related risks, which harmfully affect their health and nursing quality. Objectives: This study aimed to explore and describe perceptions of nurses on occupational health hazards and safety practices in Ditsobotla public hospitals of North West province. Method: An exploratory, descriptive, qualitative research design was undertaken in this study. An explorative design allowed the researcher to identify key issues regarding nurses' perceptions on occupational health hazards and safety practices using Donabedian structure, process and outcome. A total of 15 nurses of different categories participated in the study that formed four focus group discussions. Semi-structured focus group discussions of three to four participants were conducted until data saturation is obtained and at the point where no new themes from participants' perceptions emerged. Creswell and Clark framework of data analysis was used to analyse data. Results: Three major categories emerged during data analysis: nurse's perception on occupational health hazards in the health settings, Donabedian framework on assessing the quality of care in relation to occupational health hazards and occupational health and safety (OHS) practices. Eight themes were identified. Conclusion: Nurses' perceived different occupational hazards that affect their normal duties and responsibility in the workplace. Future interventions such as training and education on OHS policy should be adopted to promote health and well-being of the staff.